A new sliding mode controller for the DC to DC flyback converter - Şeker, Murat; Zergero?lu, Erkan (My University, 2011)
In this work, we have investigated the dynamics behavior and the control problem of a specific type of DC to DC converters known as the flyback converter. Flyback converters are basically a transformer-isolated version of the standard buck-boost converter. As opposed to the classical sliding mode controllers used for DC/DC converters, we proposed an alternative sliding mode controller that takes the combination of the output voltage and the intermediate transformer output current as the error signal to be regulated. Simulation results are presented to illustrate the effectiveness of the proposed method. © 2011 IEEE. © 2011 Elsevier B.V., All rights reserved.
2011 7th IEEE International Conference on Automation Science and Engineering, CASE 2011 -- Trieste -- 87527
Keywords: Buck boost converter; Control problems; DC-to-DC converters; Dynamics behavior; Error signal; Flyback converters; Intermediate transformer; Output current; Output voltages; Sliding mode controller; Behavioral research; Controllers; Electric autotransformers; Electric converters; Sliding mode control; DC-DC converters